Epistemologies of Empowerment: Feminist Re-Visions of the Divine in Amish Tripathi’s Shiva Trilogy - R, Vijay Karthic (ILN Journal: Indian Literary Narratives, 2024)
The paper titled Epistemologies of Empowerment: Feminist Re-Visions of the Divine in Amish Tripathi’s Shiva Trilogy explores the feminist reimagining of the divine feminine in Amish Tripathi’s Shiva Trilogy, emphasizing the empowering roles of characters like Sati and Kali within a contemporary retelling of Hindu mythology. By examining the epistemologies of empowerment embodied in these characters, the analysis delves into how Tripathi disrupts traditional patriarchal constructs surrounding femininity, divinity, and power. Sati and Kali are portrayed not as passive figures but as dynamic, empowered individuals whose resilience and strength challenge the restrictive roles typically assigned to women in myth. This paper examines Tripathi’s nuanced portrayal of female agency, solidarity, and self-worth as it redefines the feminine divine, encouraging readers to reconsider the transformative potential of mythology in reflecting and inspiring feminist ideals. Ultimately, the work illustrates how Tripathi’s reinterpretation of these mythological figures transcends traditional narratives, providing a framework through which ancient myths can be engaged as living texts, relevant to contemporary discussions on gender and empowerment.